Antecedent of Organizational Citizenship Behavior (OCB): Leadership, Organizational Commitment and Organizational Culture - Bakhri, Syaiful (Journal of Business Innovation and Research, 2023)
The current dynamics of the work need flexibility from human resource who are not only able to carry out tasks according to their job descriptions but also other additional positive behavior. This study aims to analyze the factors that influence the emergence of organizational citizenship behavior (OCB). This research uses a qualitative method, namely library research through searching for references that are in accordance with the variables reviewed using an electronic database in the 2018-2022 period which is contained in Google Scholar. The results showed that the variables of leadership, organizational commitment, and organizational culture were the antecedents of organizational citizenship behavior.Keywords : Leadership, organizational commitment, organizational culture, organizational citizenship behaviorJEL Code: O15